Inflation-Deflation Episodes in the Hengill and Hrómundartindur Volcanic Complexes, SW Iceland - Ducrocq, Cécile; Geirsson, Halldór; Árnadóttir, Thóra; Juncu, Daniel; Drouin, Vincent; Gunnarsson, Gunnar; Kristjánsson, Bjarni R.; Sigmundsson, Freysteinn; Hreinsdóttir, Sigrún; Tómasdóttir, Sigrún; Blanck, Hanna (Frontiers in Earth Science, 2021)
Non-eruptive uplift and subsidence episodes remain a challenge for monitoring and hazard assessments in active volcanic systems worldwide. Sources of such deformation may relate to processes such as magma inflow and outflow, motion and phase changes of hydrothermal fluids or magma volatiles, heat transfer from magmatic bodies and heat-mining from geothermal extraction. The Hengill area, in southwest Iceland, hosts two active volcanic systems, Hengill and Hrómundartindur, and two high-temperature geothermal power plants, Hellisheiði and Nesjavellir. Using a combination of geodetic data sets (GNSS and InSAR; Global Navigation Satellite Systems and Interferometry Synthetic Aperture Radar, respectively) and a non-linear inversion scheme to estimate the optimal analytical model parameters, we investigate the ground deformation between 2017–2018. Due to other ongoing deformation processes in the area, such as plate motion, subsidence in the two geothermal production fields, and deep-seated source of contraction since 2006, we estimate 2017–2018 difference velocities by subtracting background deformation, determined from data spanning 2015–2017 (InSAR) or 2009–2017 (GNSS). This method highlights changes in ground deformation observed in 2017–2018 compared to prior years: uplift signal of $\sim$10 km diameter located in the eastern part of the Hengill area, and geothermal production-related temporal changes in deformation near Húsmúli, in the western part of the Hengill area. We find an inflation source located between the Hengill and Hrómundartindur volcanic complexes, lasting for $\sim$5 months, with a maximum uplift of $\sim$12 mm. Our model inversions give a source at depth of $\sim$6--7 km, located approximately in the same crustal volume as an inferred contracting source in 2006–2017, within the local brittle-ductile transition zone. No significant changes were observed in local seismicity, borehole temperatures and pressures during the uplift episode. These transient inflation and deflation sources are located $\sim$3 km NW from a source of non-eruptive uplift in the area (1993–1999). We consider possible magmatic and hydrothermal processes as the causes for these inflation-deflation episodes and conclude that further geophysical and geological studies are needed to better understand such episodes.